SURVEI KEPUASAN LULUSAN TERHADAP KUALITAS PELAYANAN DI PERGURUAN TINGGI: UPAYA EVALUASI, PENGENDALIAN, DAN PENINGKATAN MUTU LEMBAGA - Imam Safi'i; Budhi Akbar; Ishaq Nuriadin; Subali Subali (Manajemen Pendidikan, 2022)
The purpose of this article is to describe the results of research on graduate satisfaction from a Postgraduate School under the auspices of one of the private universities in Jakarta. The various components explored are in the form of graduate satisfaction with leaders, lecturers, education staff, employees, infrastructure, and the impact of the studies they have taken on career advancement. This study uses a survey method through instruments developed and distributed to respondents using the google form media. The number of respondents in this study was 222. The results showed that most of the alumni or graduates of the 2019/2020 academic year were very satisfied with the service, provision of facilities and infrastructure and the impact of studies on career advancement. The average level of alumni satisfaction is 90.1. The results of this study can be used as a part of evaluating, controlling, and improving the quality of institution services to users or students.